Domestic Public Debt in Low-Income Countries : Trends and Structure - Bua, Giovanna (World Bank, Washington, DC, 2014)
This paper introduces a new data set on the stock and structure of domestic debt in 36 low-income countries over the period 1971-2011. It characterizes the recent trends regarding the do-mestic public debt of low-income countries and explores the relevance of different arguments put forward on the benefits and costs of government borrowing in local public debt markets. The main stylized fact emerging from the data is the increase in domestic government debt since 1996. It is also observed that poor countries have been able to increase the share of long-term in-struments over time and that maturity lengthening went together with a decrease in borrowing costs. However, the concentration of the investor base, mainly dominated by commercial banks and the central bank, may crowd out lending to the private sector.